Створення, підтримка та просування наукового періодичного видання - Проскудіна, Галина; Овдій, Ольга (Видавництво Львівської політехніки, 2016)
We consider the requirements and recommendations to sites of scientific periodicals with respect to their inclusion to the international abstract and citation databases such as Scopus. We conduct analysis of the current state of Ukrainian scientific periodicals sites and their including into citation databases. The typical solution for scientific periodicals sites based on OJS software is presented. It was deployed on Amazon cloud. The technological solutions for integrated centralized management support of these sites is proposed. Guidelines for creation and maintenance of scientific periodicals sites is offered.
Keywords: наукова періодика; наукова інформація; наукометричні бази даних; наукометричні показники; бібліотечні та семантичні веб-технології; хмарні технології